Efficacy of Dapagliflozin on Renal Function and Outcomes in Patients With Heart Failure With Reduced Ejection Fraction: Results of DAPA-HF. Issue 4 (26th January 2021) - Jhund, Pardeep S.; Solomon, Scott D.; Docherty, Kieran F.; Heerspink, Hiddo J.L.; Anand, Inder S.; Böhm, Michael; Chopra, Vijay; de Boer, Rudolf A.; Desai, Akshay S.; Ge, Junbo; Kitakaze, Masafumi; Merkley, Bela; et al.
Abstract : Background: Many patients with heart failure and reduced ejection fraction (HFrEF) have chronic kidney disease that complicates pharmacological management and is associated with worse outcomes. We assessed the safety and efficacy of dapagliflozin in patients with HFrEF, according to baseline kidney function, in the DAPA-HF trial (Dapagliflozin and Prevention of Adverse-outcomes in Heart Failure). We also examined the effect of dapagliflozin on kidney function after randomization. Methods: Patients who have HFrEF with or without type 2 diabetes and an estimated glomerular filtration rate (eGFR) ≥30 mL·min –1 ·1.73 m –2 were enrolled in DAPA-HF. We calculated the incidence of the primary outcome (cardiovascular death or worsening heart failure) according to eGFR category at baseline (<60 and ≥60 mL·min –1 ·1.73 m –2 ) and used eGFR at baseline as a continuous measure, as well. Secondary cardiovascular outcomes and a prespecified composite renal outcome (≥50% sustained decline eGFR, end-stage renal disease, or renal death) were also examined, along with a decline in eGFR over time. Results: Of 4742 patients with a baseline eGFR, 1926 (41%) had eGFR <60 mL·min –1 ·1.73 m –2 . The effect of dapagliflozin on the primary and secondary outcomes did not differ by eGFR category or examining eGFR as a continuous measurement. The hazard ratio (95% CI) for the primary end point in patients with chronic kidney disease was 0.71 (0.59–0.86) versus 0.77 (0.64–0.93) in those with an eGFR ≥60 mL·min –1 ·1.73 m –2 (interaction P =0.54). The composite renal outcome was not reduced by dapagliflozin (hazard ratio=0.71 [95% CI, 0.44–1.16]; P =0.17) but the rate of decline in eGFR between day 14 and 720 was less with dapagliflozin, –1.09 (–1.40 to –0.77) versus placebo –2.85 (–3.17 to –2.53) mL·min –1 ·1.73 m –2 per year ( P <0.001). This was observed in those with and without type 2 diabetes ( P for interaction=0.92). Conclusions: Baseline kidney function did not modify the benefits of dapagliflozin on morbidity and mortality in HFrEF, and dapagliflozin slowed the rate of decline in eGFR, including in patients without diabetes. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT03036124. Abstract : Supplemental Digital Content is available in the text.